Keanekaragaman jenis pohon pada hutan terfragmentasi di kawasan hutan dengan tujuan khusus (KHDTK) hutan diklat Bukit Suligi Kabupaten Rokan Hulu - Binti Masruroh; Nurul Qomar; Sri Wulandari (Program Studi Ilmu Lingkungan, Program Pascasarjana Universitas Riau, 2022)
KHDTK Hutan Diklat Bukit Suligi is located in Dayo Village, Tandun District, Rokan Hulu Regency. Based on decree number 729/Menhut-II/2009 the area of ​​the Bulit Suligi Education and Training Forest KHDTK is 2,183 ha, but because of spirit of reform and regional autonomy in 1998, the community began to carry out illegal logging and illegal occupation by clearing forests into oil palm plantations. As a result, the fragmented forest area become 704.30 ha. The purpose of this study was to identifying the composition and diversity of tree species in this area. This study uses a quantitative approach using primary and secondary data. Primary data were collected using nested sampling with a large plot of 20 x 20 meters to count trees and a small plot of 10 x 10 meters to count poles. Identification of species composition was carried out by calculating the Important Value Index (IVI), while tree species diversity was calculated using the Shanon-Winner diversity index. The results showed that the dominant species at the pole level was Medang (Litsea angulana Blume) with an IVI of 28,26%, while the species that dominated at the tree level was Meranti Merah (Shorea lepidota) with an IVI of 24,43%. The tree level diversity index of 3,61 and the pole diversity index of 3,66 are included in the high diversity category, its means that the distribution of individuals for each species is evenly distributed or the number of individuals found is close to uniform. This condition also illustrates that the forest communiy is in a stable condition. Keywords: Bukit Suligi, Fragmented, Tree, Diversity